NUMERICAL CALCULATIONS OF TEMPERATURES AND STRESSES IN CRYSTALLIZING INGOT FROM STEEL 20HN3A WITH SIZE 300X400 MM FOR DIFFERENT CONDITIONS OF COOLING - A. N. Chichko; N. V. Andrianov; A. V. Demin; D. M. Kukuj; V. F. Sobolev; Ju. V. Jatskevich; O. I. Chichko (Литьë и металлургия, 2004)
The results of the computer calculations of the temperature and stress fields, of the crystallizing steel ingot of size 300x400 mm from steel 20ХНЗЛ at circular-flame and flat flame jet-type cooling, are presented. The comparative analysis of the stresses changes along the whole length of ingot for two types of jet-type cooling at the example of the machine of the continuous slugs casting BMZ.